KAJIAN POTENSI HUTAN MANGROVE PARIT BELIDA DAN PENGEMBANGAN BAHAN AJAR EKOSISTEM - Kahar, Adi Pasah; Rustaman, Nuryani Y.; Supriatno, Bambang (Universitas Sebelas Maret, 2014)
Abstract - This research is conducted because of the limited information of mangrove forest in Parit Belida and the damage caused by the lack of society awarness. Based on the preliminary research, those are due to the irrelevant prior knowledge and information transfer. Mangrove forest in Parit Belida provides facts on the ground and biological object materials which are relevant with the topic of ecosystem. It has various plants and animals with special morphology, various types of adaptation, and the physical characteristics of the mangrove forest itself. However those can not be directly applied to the learning process. It needs to be processed into functional materials which allows the students to understand the concept of the fact presented in the teaching materials. The R&D method was used to obtain teaching material initiated with preliminary study, composing draft, development, validation and program implementation. As Curriculum 2013 said that teaching learning process should develop character education and scientific approach for students, the concept and the attitude of the students towards the awarness of mangrove forests can be improved by involving them actively and innovatively. The development of teaching materials based on the facts and potency of local mangrove forest could create the conservation characteristic of students Keywords : mangrove forest in Parit Belida, teaching material, conservation characteristic